TINGKAT PENGETAHUAN IBU TENTANG KEJANG DEMAM PADA ANAK USIA 6 BULAN SAMPAI 5 TAHUN DI PUSKESMAS KAMPAR TIMUR 2018 - Putri Wulandini; Roni Saputra; Dayana Frilianova (LPPM Universitas Abdurrab, 2019)
Febrile seizures is a disease that is quite common in infants. Half of the occurrence of febrile seizures occur recurrent febrile seizures, this occurs because the child's brain development is still not optimal enough in doing self-defense against the fever, resulting in the rise of febrile seizures. Parents often panic facing the event of febrile seizures. handling fever in children is very dependent on the parents. Level of knowledge of each different mother will lead to the management of fever in different children. This study aims to determine the level of knowledge of the mother about febrile seizures in children aged 6 mounth to 5 years in Puskesmas Kampar East Kampar District in 2018. this research use accidental sampling sampling technique and data collection is done by questioner. The research was conducted on 30 May - 9 June 2018 at Puskesmas Kampar East Kampar District. Sample was 50 respondents with univariate data analysis. The results of this study indicate that the mother's knowledge level is less with the number of 36 people (72%). It is hoped for the Puskesmas to be able to make extantion program about things related to febrile definition dan febrile seizures. And for the mother around Puskesmas Kampar East Kampar District is expected to be more open to new information and more accepting suggestion from nurse and medical officer that exist, especially about information that is important and useful for family health. Key Word : Level knowledge of mother, Febrile seizures